Simple synthesis of 32P-labelled inositol hexakisphosphates for study of phosphate transformations - Whitfield, H; Riley, A; Diogenous, S; Godage, H; Potter, B; Brearley, C (Springer, 2017)
Background and aims In many soils inositol hexakisphosphate in its various forms is as abundant as inorganic phosphate. The organismal and geochemical processes that exchange phosphate between inositol hexakisphosphate and other pools of soil phosphate are poorly defined, as are the organisms and enzymes involved. We rationalized that simple enzymic synthesis of inositol hexakisphosphate labeled with 32P would greatly enable study of transformation of soil inositol phosphates when combined with robust HPLC separations of different inositol phosphates. Methods We employed the enzyme inositol pentakisphosphate 2-kinase, IP5 2-K, to transfer phosphate from [γ-32P]ATP to axial hydroxyl(s) of myo-, neo- and 1Dchiro-inositol phosphate substrates. Results 32P-labeled inositol phosphates were separated by anion exchange HPLC with phosphate eluents. Additional HPLC methods were developed to allow facile separation of myo-, neo-, 1D-chiro- and scyllo-inositol hexakisphosphate on acid gradients. Conclusions We developed enzymic approaches that allow the synthesis of labeled myoinositol 1,[ [32P]2,3,4,5,6-hexakisphosphate; neo-inositol 1,[ 32P]2,3,4,[32P]5,6 – hexakisphosphate and 1D-chiro-inositol [32P]1,2,3,4,5,[ 32P]6-hexakisphosphate. Additionally, we describe HPLC separations of all inositol hexakisphosphates yet identified in soils, using a collection of soil inositol phosphates described in the seminal historic studies of Cosgrove, Tate and coworkers. Our study will enable others to perform radiotracer experiments to analyze fluxes of phosphate to/from inositol hexakisphosphates in different soils.